A bridge to higer mathematics - Deaconu, Valentin; Pfaff, Donald C. (2017)
This is an introduction to proofs book for the course offering a transition to more advanced mathematics. It contains logic, sets, functions, relations, the construction of rational, real and complex numbers and their properties. It also has a chapter on cardinality and a chapter on counting techniques. The book explains various proof techniques and has many examples which help with the transition to more advanced classes like real analysis, groups, rings and fields or topology.--
"A Chapman & Hall book."
Keywords: Proof theory -- Textbooks; Logic, Symbolic and mathematical -- Textbooks; Mathematics -- Textbooks